2013
DOI: 10.1038/srep01978
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage tissue engineering identifies abnormal human induced pluripotent stem cells

Abstract: Safety is the foremost issue in all human cell therapies, but human induced pluripotent stem cells (iPSCs) currently lack a useful safety indicator. Studies in chimeric mice have demonstrated that certain lines of iPSCs are tumorigenic; however a similar screen has not been developed for human iPSCs. Here, we show that in vitro cartilage tissue engineering is an excellent tool for screening human iPSC lines for tumorigenic potential. Although all human embryonic stem cells (ESCs) and most iPSC lines tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…Indeed, the heterogeneity of in vitro chondrogenesis may preclude our understanding of the mechanisms by which genetic variation can impact cartilage development and arthritis progression. Previous attempts to purify iPSC-derived CPs relied on many rounds of sorting multiple surface markers, using reporter constructs that are activated by minimal promoter regions of chondrocyte markers, or physical dissection of self-aggregating chondroprogenitors [20,29,37,49,50]. During chondrocyte differentiation, COL2A1 expression is regulated by concerted coordination of promoter regions, distal and intronic enhancers, and UTRs [5153].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the heterogeneity of in vitro chondrogenesis may preclude our understanding of the mechanisms by which genetic variation can impact cartilage development and arthritis progression. Previous attempts to purify iPSC-derived CPs relied on many rounds of sorting multiple surface markers, using reporter constructs that are activated by minimal promoter regions of chondrocyte markers, or physical dissection of self-aggregating chondroprogenitors [20,29,37,49,50]. During chondrocyte differentiation, COL2A1 expression is regulated by concerted coordination of promoter regions, distal and intronic enhancers, and UTRs [5153].…”
Section: Discussionmentioning
confidence: 99%
“…60 Efforts to derive iPSCs from adult chondrocytes using nonintegrating methods such as mRNA delivery may address some of these concerns, 61 and methods to isolate successfully differentiated cells can add additional control over the phenotype of cells transplanted for therapy. 62,63 Indeed, the multi-step differentiation strategy employed in this study uses positive selection with a Col2 reporter as an additional safeguard to exclude nondifferentiated iPSCs.…”
mentioning
confidence: 99%
“…Another report on 21 human iPSC lines and 6 human ESC lines indicated that certain human iPSC clones were in a pro-oncogenic state, as shown by the ectopic presence of secretory tumor tissue during in vitro cartilage differentiation [109] . These reports together implied that a marker foreseeing pro-oncogenic differences in iPSC lines would be required for establishing safe therapy using iPSCs.…”
Section: Selecting the Most Appropriate Ipsc Line For Clinical Usementioning
confidence: 99%